Strengthening the role of community health assistants in delivering primary health care: the case of maternal health services in Zambia - Olatubosun Akinola; Nelia Banda; Adam Silumbwe; Chama Mulubwa; Malizgani Paul Chavula; Hilda Shakwelele; Sylvia Chila; Joseph Mumba Zulu (BMC Primary Care)
Abstract Introduction Many low-and middle-income countries, including Zambia experience a huge deficit of human resource for health, which affects the delivery of primary health care services such as maternal and child health (MCH), nutrition, HIV and gender-based services. The Clinton Health Access Initiative in collaboration with the Zambian Ministry of Health implemented a community health systems (CHS) strengthening project to enhance the capacity of community health assistants (CHA) to provide MCH services from 2019 to 2021. The project activities included capacity building in supervision, provision of financial incentives and logistics. This study explores how these interventions strengthened the role of the CHAs in delivering MCH services. Methodology This was a qualitative study consisting of 189 KIIs and IDIs as well as 20 FGDs conducted in all the 10 provinces of Zambia with the CHAs, and their supervisors, health workers, neighbourhood health committees and community members. Data were analysed using thematic analysis. Results The CHS strengthening interventions including provision of training manuals, streamlined recruitment and deployment policies, capacity building of CHA supervisors, provision of transport and monthly remuneration contributed to improved delivery and acceptability of MCH services. Further, the leveraging of community networks, linkages and partnerships when delivering these services, including the traditional and religious leaders contributed to improved coverage and acceptability of MCH services. Meanwhile, health systems barriers such as limited supplies in some health facilities, shortage of health workers, persistent transportation challenges and failure to fully abide by the CHA recruitment and selection criteria affected delivery and acceptability of MCH services. Conclusion This study builds on existing evidence on the importance of building a stronger community–based primary health care to effectively address maternal and child health related issues. We emphasize the need to integrate strategies such as provision of training manuals, enhanced recruitment and deployment policies, capacity building of supervisors, provision of transport and remuneration within the CHA program to enhance the provision and acceptability of health services.